Gagasan Sekularisasi Politik Ibn Taymiyah - Muhammad Arif (LP2M UIN Sunan Kalijaga, 2017)
Nearly all Islamists, Islamic scholars, agree that the concept of political secularization is unobserved in the tradition of medieval Islamic thoughts. Yet, this does not mean that there was no concept on political secularization at all during that period. Support for political secularization is, for instance, found in the views of Ibn Taymiyah, one of the prominent Islamic thinkers in the medieval era. For this reason, I am interested in conducting further study on the subject matter in this article. This article employed the method of literature review analysis by examining works by Ibn Taymiyah, particularlyMinhaj al-Sunnah al-Nabawiyah fi naqdh kalam al-Syi’ah wa’l-Qadariyahand other relevant references. In analyzing the collected data, I utilized two approaches: existential phenomenology and historical continuity. This article found that there are at least four impressions in Ibn Taymiyah’s thoughts that may be stated as oriented toward political secularization. Firstly, Ibn Taymiyah understood that imamahis not a matter of religion or faith. Secondly, Ibn Taymiyah stated that Islamic sharia is the responsibility of the ummah not a matter of imamah. Thirdly, Ibn Taymiyah said that the presence of the Prophet Muhammad in this world is merely as a prophet or messenger of God and not as an Imam or political leader. Fourthly, Ibn Taymiyah initiated an electoral mechanism that does not prioritize religious aspects.[Hampir semua Islamis, pengkaji Islam, sepakat bahwa dalam tradisi pemikiran Islam pertengahan tidak dijumpai adanya gagasan sekularisasi politik. Namun, bukan berarti tidak pernah ada gagasan tentang sekularisasi politik dalam tradisi pemikiran politik Islam pertengahan. Dukungan atas sekularisasi politik ini misalnya dapat dijumpai dalam pemikiran Ibn Taymiyah, salah satu dari pemikir Islam pada era pertengahan. Oleh karena itu, penulis tertarik untuk mengkajinya lebih lanjut dalam artikel ini. Artikel ini menggunakan metode kajian berbasis pustaka, yaitu dengan menelaah karya-karya Ibn Taymiyah, terutama Minhaj al-Sunnah al-Nabawiyah fi naqdh kalam al-Syi’ah wa’l-Qadariyah serta referensi-referensi lain yang terkait. Dalam menganalisis data-data yang terkumpul penulis menggunakan dua pendekatan, yaitu: fenomenologi eksistensial dan kesinambungan historis. Artikel ini menemukan bahwa setidaknya ada empat jejak dalam pemikiran Ibn Taymiyah yang dapat dikatakan mengarah pada sekularisasi politik. Pertama, Ibn Taymiyah memahami bahwa imamah bukan merupakan urusan agama atau keimanan. Kedua, Ibn Taymiyah mengatakan bahwa syari’ah Islam adalah tanggungjawab ummah bukan urusan imamah. Ketiga, Ibn Taymiyah mengatakan bahwa keberadaan Nabi Muhammad di dunia ini hanyalah sebagai seorang nabi atau utusan Allah dan bukan sebagai seorang Imam atau pemimpin politik. Keempat, Ibn Taymiyah memunculkan mekanisme pemilihan pemimpin yang tidak mengutamakan sisi agama.]